(untitled) (Medical Forum Monthly, 2024)
Objective: To study the protective effects of taurine in oxytetracycline induced hepatic steatosis in albino rats. Study Design: Prospective Experimental Study. Place and Duration of Study: This study was conducted in the Department of Anatomy, Khyber Medical College, Peshawar from July 2011-December 2011. Materials and Methods: Four groups of male albino rats, each comprising 8 animals, were treated for 21 days as follows: Group A served as control, group B treated with oxytetracycline 120 mg/kg body weight intraperitoneally for three consecutive days, group C treated with oxytetracycline 120mg/kg body weight intraperitoneally for three consecutive days plus taurine 1% solution as their sole source of drinking water for 21 days, and group D treated with taurine 1% solution alone as their sole source of drinking water for 21 days. The animals were weighed at the start and end of treatment and were sacrificed on 22nd day of start of treatment under deep ether anaesthesia. Blood samples were collected for enzyme study by intracardiac puncture. The livers were removed, washed in normal saline and weighed. They were fixed in 10% formalin and embedded in paraffin. 4 μ thick sections were cut and processed for H & E staining, and were examined microscopically. Statistical analysis of the data was done and results were tabulated. Results: Groups A (data not shown) and D showed normal results with no significant differences across the groups. The relative liver weights in group B increased significantly (P value <0.05) in comparison with group C and D. The relative liver weights decreased significantly (P value <0.05) in group C and D as compared to group B. There was moderately significant decrease (P value <0.01) in the values of serum hepatic enzymes (SGPT, SGOT, and ALP) in the animals of group C as compared to group B. Histologically the livers of group B animals showed generalized microvesicular steatosis. In group C the fatty change was much less pronounced as compared to group B. Conclusion: The data show that the hepatic steatosis induced by oxytetracycline can be reversed / attenuated by taurine supplementation for 21 days, in albino rats.